If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5x + 14 = 59 Reorder the terms: 14 + -5x = 59 Solving 14 + -5x = 59 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-14' to each side of the equation. 14 + -14 + -5x = 59 + -14 Combine like terms: 14 + -14 = 0 0 + -5x = 59 + -14 -5x = 59 + -14 Combine like terms: 59 + -14 = 45 -5x = 45 Divide each side by '-5'. x = -9 Simplifying x = -9
| x=3/x/2 | | 3y+12=33 | | 2x-10=4x+18 | | 12(1-8p)=-6p-4(-8p-3) | | (7a^4-6a^3+1)+(3a^3-2a+1)= | | 0.35y=2.80 | | 2x=-4(11+5x) | | (n/y-c)/n | | 2(1)+5+3x-3=5x+9 | | 1/3×=2 | | 11=5m-6-7m+9 | | 18=6-6x+3x | | 14-(x+m)=3(x+9)-(-1)10 | | .05x+.25y=2.85 | | 7x+2-6x-5= | | 1.08+n=15.75 | | 5(-1)+9= | | 80+39+x=180 | | 21.3+r=1.51 | | -d/5-5d/6 | | (X+6)(x+2)=192 | | 2/3x=x-150 | | sqrt(3x/50) | | z/5=12/5 | | 64x^2-96x+36= | | -16+3x=-2+9 | | 8-8x=-56 | | 3x-53=25 | | 8x^2+37-15=0 | | f(x)=4x-25 | | y/-6=-4/3 | | 4x+13=65 |